DIGITAL SIGNATURE PADA KARTU TANDA PENDUDUK - Junaidi Surya (JURNAL AKADEMIKA)
Digital Signature in this time represent a inportant component in a digital document, requirement for this signature progressively strengthened because progressively expand technological of information, conducive of document spreading easy to and free. Digital signature follow the nature of applicable conventional signature in digital document. Such Signature perhaps non habit signature which in the scan into digital format, but signature applied the concepts Cryptography. Digital Signature gift can exploit the system of cryptography and message digest 5 (MD5) by using public key symmentrically in yielding same output 128 beet without your Exellency how many string include to get the value hashing